2021
DOI: 10.18805/ajdfr.dr-1773
|View full text |Cite
|
Sign up to set email alerts
|

​Development and Nutritional Evaluation of Foxtail Millet (Setaria italica) based Laddu

Abstract: Backround: Foxtail millet (Setaria italica) is known for its health benefits as it is nutritionally superior to conventional food grains. Laddu are ball-shaped sweets which are popular in India and are often served at festive or religious occasions. Hence, an attempt was made to develop foxtail millet based value added laddu. Methods: Besan laddu was taken as control. Optimized foxtail millet laddu were nutritionally evaluated for proximate composition, sugars and minerals. Paired ‘t’ test was used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The range of bulk density of MBMP was higher than that of MFMP because of the greater proportion of fines in the former. Tumwine et al (2019) reported bulk density of 600 kg/m 3 for millet‐SMP composite flour, while Sudha et al (2021) reported a value of 630 kg/m 3 for foxtail millet flour. The bulk density of MFMP and MBMP was lower because of lower TS used in spray drying and the relatively larger occluded air content in these powders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The range of bulk density of MBMP was higher than that of MFMP because of the greater proportion of fines in the former. Tumwine et al (2019) reported bulk density of 600 kg/m 3 for millet‐SMP composite flour, while Sudha et al (2021) reported a value of 630 kg/m 3 for foxtail millet flour. The bulk density of MFMP and MBMP was lower because of lower TS used in spray drying and the relatively larger occluded air content in these powders.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of malted millets into milk to make convenient and healthy foods provides better nutritional balance and value addition, besides enabling product diversification of millets (Sudha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation